Development of XANES nanoscopy on BL7C at PLS‐II. (20th February 2020) - Park, Jae Yeon; Singh, Jitendra Pal; Lim, Jun; Lee, Sangsul
Abstract : The development status of XANES nanoscopy on BL7C at Pohang Light Source‐II (PLS‐II) and an explanation of this experimental technique through analysis of the battery‐material example are presented. Abstract : X‐ray absorption near‐edge structure (XANES) imaging is a powerful tool to visualize the chemical state distribution of transition‐metal‐based materials at synchrotron radiation facilities. In recent years, the electrochemical working rechargeable battery has been the most studied material in XANES imaging owing to the large increase of portable electronics and electric vehicles. This work acknowledges the importance of battery analysis and has developed the XANES imaging system on BL7C at Pohang Light Source‐II (PLS‐II). BL7C employs an undulator taper configuration to obtain an energy band >130 eV near the K ‐absorption edge of the target element with a minimum energy interval >0.2 eV. While measuring energy‐dependent images, the zone plate translation maintains the best focus, and then various data processes such as background correction, image registration and clustering allow single XANES spectrum extraction and chemical distribution mapping. Here, the XANES imaging process is described, the XANES spectrum quality is identified and the chemical states of the partially charged cathode material used in lithium‐ion batteries as an application example are examined.